2014
DOI: 10.7205/milmed-d-14-00044
|View full text |Cite
|
Sign up to set email alerts
|

2-Point Ultrasonography to Confirm Correct Position of the Gastric Tube in Prehospital Setting

Abstract: The 2-point ultrasonographic live control of the GT position has a better sensitivity and a much higher specificity than the syringe test but similar to the xiphoid ultrasound control. However, our method allows to show the GT in the esophagus and to use the dynamic ultrasound fogging to reveal an intragastric position that was not obvious with the common techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 17 publications
3
37
0
4
Order By: Relevance
“…Mean confirmation time of GT position was 18 seconds [15]. In our study, we also found similar results those found in the study by Brun et al (2014). In our study, gastric USG failed to confirm the accurate position of GT in seven patients due to full stomach and gas intervention.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Mean confirmation time of GT position was 18 seconds [15]. In our study, we also found similar results those found in the study by Brun et al (2014). In our study, gastric USG failed to confirm the accurate position of GT in seven patients due to full stomach and gas intervention.…”
Section: Discussionsupporting
confidence: 88%
“…In a study performed in 132 patients by Brun et al (2014), the position of GT was confirmed in esophagus in 100% of all patients and in stomach in 62.5% through USG. Mean confirmation time of GT position was 18 seconds [15]. In our study, we also found similar results those found in the study by Brun et al (2014).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations